2020
DOI: 10.1096/fj.201903210r
|View full text |Cite
|
Sign up to set email alerts
|

A SNARE protein Syntaxin 17 captures CFTR to potentiate autophagosomal clearance under stress

Abstract: Macroautophagy, or simply autophagy, is a catabolic program for restoring cellular resources and energy balance as cells recognize damaged organelles, protein aggregates, and invading pathogens. 1,2 As new studies emerge, the role of autophagy has been expanded to include cell growth, cell development and aging, tumor suppression, and immunity among others. 2 Cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride channel present in the lung and intestinal epithelial cells and forms a key tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Syntaxin 5 (STX5) overexpression has been shown to stimulate unconventional trafficking of core-glycosylated ∆F508-CFTR to the PM [ 35 ]. Syntaxin-17 (STX17), a SNARE protein, interacts with CFTR [ 52 ] and the loss of the CFTR-STX17 interaction impairs bacterial clearance and could play a critical role in infectious diseases among CF patients. Syntaxin-12 (STX12) and STX6 form a SNARE complex that regulates transport between late endosomes and the trans-Golgi network.…”
Section: Resultsmentioning
confidence: 99%
“…Syntaxin 5 (STX5) overexpression has been shown to stimulate unconventional trafficking of core-glycosylated ∆F508-CFTR to the PM [ 35 ]. Syntaxin-17 (STX17), a SNARE protein, interacts with CFTR [ 52 ] and the loss of the CFTR-STX17 interaction impairs bacterial clearance and could play a critical role in infectious diseases among CF patients. Syntaxin-12 (STX12) and STX6 form a SNARE complex that regulates transport between late endosomes and the trans-Golgi network.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we aimed to discuss current knowledge of how distinct steps of the autophagy-lysosomal process are regulated by ion transporters ( Figure 1 ). For brevity, we mostly excluded tissue-specific ion channels such as the plasma membrane CFTR or ER-localized RyR, which are reported to influence autophagy in specific tissue types [ 159 , 160 ]. A few regulatory nodes become clear if we look at ion channel regulation of autophagy (summarized in Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macroautophagy (canonical autophagy) occurs inside a double membrane structure called an autophagosome. Multiple studies have demonstrated defective autophagy in CF phagocytes and other cells, with the critical restoration of macrophage properties through autophagy manipulation [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ].…”
Section: Specialized Vacuoles: Autophagy and Lc3-associated Phagocyto...mentioning
confidence: 99%
“…Syntax 17 (Stx17) is required for fusion with the lysosome; lack of Stx17 causes the accumulation of autophagosomes without degradation [ 166 ]. In a study conducted by Arora et al using epithelial cells, Stx17 was associated with CFTR at a late stage of autophagy to mediate bacterial clearance [ 133 ]. Whether these interactions are conserved in CF macrophages has not yet been determined.…”
Section: Specialized Vacuoles: Autophagy and Lc3-associated Phagocyto...mentioning
confidence: 99%